2010
DOI: 10.1111/j.1365-2222.2010.03541.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of childhood asthma: are they real?

Abstract: It has been suggested that there are several distinct phenotypes of childhood asthma or childhood wheezing. Here, we review the research relating to these phenotypes, with a focus on the methods used to define and validate them. Childhood wheezing disorders manifest themselves in a range of observable (phenotypic) features such as lung function, bronchial responsiveness, atopy and a highly variable time course (prognosis). The underlying causes are not sufficiently understood to define disease entities based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 108 publications
(174 reference statements)
3
101
1
4
Order By: Relevance
“…A multidimensional approach combining clinical features and disease physiopathology (inflammation and remodeling), evaluated as complex parameters, has been recommended (20), which would also require to consider age and sex in such definitions.…”
Section: From Phenotypes To Endotypesmentioning
confidence: 99%
“…A multidimensional approach combining clinical features and disease physiopathology (inflammation and remodeling), evaluated as complex parameters, has been recommended (20), which would also require to consider age and sex in such definitions.…”
Section: From Phenotypes To Endotypesmentioning
confidence: 99%
“…A variety of asthma phenotypes have been recognised [8][9][10] and it has been suggested that better definitions of asthma subtypes should form the basis of treatment options for patients that have, in the past, been classified mainly by clinical severity [11]. This approach is yet to be widely adopted for clinical use, since accurate characterisation of different phenotypes is difficult and not standardised.…”
mentioning
confidence: 99%
“…Numerous recent studies have shown that phenotypes can differ in their association with asthma risk factors, 13 and, more importantly for clinical practice, phenotypes can differ in their response to long-term treatment modalities. The pressing necessity for developing a consistent and reproducible classification system would facilitate research into etiology and pathophysiology, allow targeted treatment and preventive measures, and improve the prediction of long-term outcomes.…”
Section: Pathophysiology Of Asthmamentioning
confidence: 99%
“…The term phenotype, as introduced by Johannsen and Shull, was intended to characterize different "types" of organisms distinguishable by their observable characteristics (eg, shape, structure, size, and color). 13 Today, substantial efforts are underway in the search for the variants underlying predisposition to asthma and associated phenotypes: preasthma wheezing, inflammatory markers, infections, atopy, aspirin sensitivity, exercise, severe asthma, flare-prone, lung function, elevated immunoglobulin E (IgE), highly variable time course (prognosis), and bronchial hyper-responsiveness.…”
Section: Pathophysiology Of Asthmamentioning
confidence: 99%